If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+5x=-6x+6
We move all terms to the left:
6+5x-(-6x+6)=0
We get rid of parentheses
5x+6x-6+6=0
We add all the numbers together, and all the variables
11x=0
x=0/11
x=0
| 7x/5+1=15 | | -6(4–8n)=-360 | | 8-2y=34 | | -8(3+8n)=-408 | | x−71=10(2x+3)−25 | | 8-2u=34 | | 7x–12=5x+16 | | 10=2+2q | | 286=8(1+5n)–2 | | 3=-16t^2+25t | | 3b-25=2 | | 3(4x+6)=25 | | .25(x‐13)=7 | | (1.75*x)-x=1.75 | | 1+7x=x-71 | | 9x-6=4+19 | | -10=x+-21 | | 3x+5=4×-7 | | 4.3+1=7-1.7x | | 3(2x–5)=5(x–4)+10 | | 29-5y=54 | | 9-2m=-3 | | −9(x+6)+60=10−10x | | x.60=4x | | 5=15-2m | | 18=-8y+6(y+5) | | -6e+24=-30 | | -6+2+4m-12=6 | | (x-8)(x+10)=0 | | (0.10x)+x=1.75 | | 8+4K-2k=16 | | 2.5xA=0.5 |